Physical, Mechanical, and Thermal Analysis of Polylactic Acid/Fumed Silica/Clay (1.28E) Nanocomposites - Lai, Josephine Chang Hui; Md. Rezaur, Rahman; Sinin, Hamdan (Hindawi Publishing Corporation, 2015)
Polylactic acid/fumed silica/clay (PLA/FS/clay) (1.28E) nanocomposites have been successfully prepared by solution-intercalation film-casting technique. The resultant nanocomposites were characterized by Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), tensile test, thermogravimetric analysis (TGA), and moisture absorption test. The FT-IR spectrum indicated that PLA/FS/clay with 2 wt% hadmuch broader peak compared to 5 wt%, 10 wt%, and 15wt% nanocomposites. Incorporation of clay (1.28E) with 2wt% showed the best compatibility with PLA/FS matrix. PLA/FS/clay (1.28E) nanocomposite with 2wt% of clay loading had higher tensile strength and modulus compared to other nanocomposites. The thermal stability and activation energy of 2wt% of PLA/FS/clay (1.28E) nanocomposite are the highest among all the nanocomposites. The moisture absorbed into PLA/FS/clay (1.28E) nanocomposite was significantly reduced with clay loading of 2 wt%.